Clinical features and follow-up results of the patients with methicillin-resistant Staphylococcus aureus (MRSA) in orthopedic practice - Resit Sevimli; Aydin Arslan; Yucel Duman; Mehmet Fatih Korkmaz; Mehmet Nuri Erdem (Medicine Science, 2018)
Treatment of the infections caused by methicillin-resistant Staphylococcus aureus (MRSA) strains in orthopedic patients is a difficult and laborious process for both the patient and physician. Staphylococcus aureus(S. aureus) is one of the leading causes of community-acquired and nosocomial infections. In this study, we aimed to investigate the susceptibilityof the MRSA strainsisolated in orthopedic patients cultured for different reasons in our clinic to various antibiotics, and to evaluate clinical characteristics of the patients and factors affecting the prognosis. A total of 40 patients with MRSAisolated in our orthopedics clinic between December 2012 and November 2016 were retrospectively analyzed. Data including age, sex, comorbidities, previous surgeries, and previous antibiotic treatments were obtained from patients files and electronic information system. Of 40 patients, 60% were male, and 56% were over 60 years old. While 80% of the patients underwent an orthopedic surgery, 20% of them received no surgical intervention before the diagnosis. A total of 90% were in-patients, and the mean length of hospital stay was 22 days. The mean time from the date of hospitalization to the isolation of MRSA was 12 days. According to the consultation findings, in the clinical recovery process of the patients and in the treatment algorithm given to those patients, vancomycin and teicoplanin were found to be among the most important treatment options, in addition to significant debridement to be done, for MRSA strains. Our study results suggestthat, in addition to the surgical debridement, timely antibiotherapy is of utmost importance to reduce mortality and morbidity in MRSA-positive orthopedic patients. [Med-Science 2018; 7(1.000): 162-165]